Anterior transcallosal approach to the colloid cysts of the third ventricle: Case series and review of the literature - (:unkn) unknown (GEORG THIEME VERLAG KG, 2004)
Objectives: To evaluate the results of the anterior transcallosal approach to the colloid cysts of the third ventricle. Patients and Methods: A retrospective analysis of the patients operated on between 1986 and 2003 was carried out. There were 19 patients (10 female, 9 male) with a median age of 43. The main presenting symptom was headache. One of the patients presented with acromegaly due to a pituitary tumor. The size of the cysts ranged from 15 to 43 mm. An anterior transcallosal approach was used in all patients. Results: The cysts were excised totally in all cases. Postoperatively no recent memory loss has been detected in any patient. One patient with hemorrhagic papil stasis experienced temporary visual worsening. In one patient with hydrocephalus a ventriculoperitoneal shunt was needed. One patient with postoperative superior frontal gyrus venous infarction had a seizure. The follow-up period was from 1 month to 13 years (mean 5.2 years). To date, there has been no recurrence so far. Conclusion: The anterior transcallosal approach is a safe method for the treatment of third ventricular colloid cysts.
Keywords: colloid cyst; anterior transcallosal approach; craniotomy; third ventricle; microsurgery; 3RD VENTRICLE; ENDOSCOPIC TREATMENT; INTRAVENTRICULAR TUMORS; STEREOTACTIC ASPIRATION; SURGICAL CONSIDERATIONS; MICROSURGICAL ANATOMY; THIRD VENTRICLE; REMOVAL; MANAGEMENT; RESECTION